FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU ETIS PROFESI AKUNTAN PENDIDIK (STUDI EMPIRIS PADA PERGURUAN TINGGI DI PROVINSI LAMPUNG) - Nedi Hendri; Suyanto Suyanto (Universitas Muhammadiyah Metro, 2014)
The aim of this study was to determine the various factors that influence ethical behavior accounting profession educators in Lampung Province. Analysis of the data of this study are included in the quantitative research and aimed to test the hypothesis. Structural analysis of studies using Equetion Modeling (SEM) in order to obtain a comprehensive model of research results, both direct effect and indirect effect. The results showed that moral reasoning does not significantly affect the ethical behavior accountant educator. The findings of this study are not consistent with existing theory and do not support someof the results of previous studies which claim that moral reasoning would easily make a moral judgment and moral behavior. The influence of moral reasoning on the ethical behavior of the accounting profession educators tend to be straightforward. The findings of this study are consistent with existing theory and supports some of the results of previous studies which state that will facilitate one's professional experience make moral judgment and moral behavior. Ethical attitude will automatically bring ethical behavior as well. The influence of professional experience to the ethical behavior of the accounting profession educators tend to be direct or through locus of control. Keywords:Moral thinking, professional experience, locus of control and ethical behavior.